Steps Towards the Use of TiS2 Electrodes in Ca Batteries. Issue 7 (6th March 2020) - Verrelli, R.; Black, A.; Dugas, R.; Tchitchekova, D.; Ponrouch, A.; Palacin, M. R.
Abstract : A comparative study of the reduction of TiS2 in diverse electrolyte formulations involving Ca(BF4 )2 and Ca(TFSI)2 salts was carried out at different temperatures (from 25 °C to 100 °C). While for the former salt intercalation of calcium is only observed at high temperatures, calcium intercalated phases are also observed for the latter even at room temperature. The nature of the electrolyte does also have an impact on the relative amounts of the phases formed. Since Ca(TFSI)2 based electrolytes do not enable calcium plating, cycling was attempted using activated carbon as counterelectrode, and the reversibility of the process was ascertained. Even if corrosion of stainless steel current collectors and side reactions do still prevent proper cyclability, the results achieved should contribute to the establishment of reliable and viable cell set-up and methodology for the unambiguous study of the intercalation process in multivalent battery systems.